Honeymoon Period in Newborn Rats With CDH Is Associated With Changes in the VEGF Signaling Pathway - Miura da Costa, Karina; Fabro, Alexandre Todorovic; Becari, Christiane; Figueira, Rebeca Lopes; Schmidt, Augusto F.; Ruano, Rodrigo; Sbragia, Lourenço (Frontiers in Pediatrics, 2021)
Abstract Background: Newborns with congenital diaphragmatic hernia (CDH) have a time-limited postnatal period of ventilatory stability called the honeymoon period, after which changes in pulmonary vascular reactivity result in pulmonary hypertension. The mechanisms involved in the honeymoon period are not known. Our aim was to determine the role of mechanical ventilation on vascular reactivity and VEGF signaling during the honeymoon period in a rat model of CDH. Materials and Methods: CDH was induced by nitrofen administration to pregnant rats. Newborn rats not exposed to nitrofen formed the control groups . Both were CDH and controls were either immediately euthanized or randomized to mechanical ventilation for 30, 60 or 90 minutes (n=7/group). The left lungs (n=4) were evaluated by immunohistochemistry for the pulmonary vasculature (media wall thickness), VEGF, VEGFR-1/2 and eNOS. Western blotting (n=3) was performed to quantify the expression of VEGF, VEGFR-1/2 and eNOS. Results: Controls showed a progressive reduction in media wall thickness with ventilation, while CDH temporary reduction at 30 minutes followed by an increase with the progression of the ventilatory time. CDH showed a transient decrease in VEGFR2 expression at 30 minutes and failed to progressively increased the eNOS expression as observed in controls. Conclusion: Newborn rats with CDH showed a transient improvement in the MWT which likely corresponds to the clinical honeymoon period. This transient improvement was associated with an abnormal VEGF and eNOS expression. suggesting that the VEGF-NO pathway plays a role in the honeymoon period of CDH.